Minimal-length Synthetic shRNAs Formulated with Lipid Nanoparticles are Potent Inhibitors of Hepatitis C Virus IRES-linked Gene Expression in Mice - Anne Dallas; Heini Ilves; Joshua Shorenstein; Adam Judge; Ryan Spitler; Christopher Contag; Suet Ping Wong; Richard P Harbottle; Ian MacLachlan; Brian H Johnston (Elsevier, 2013)
We previously identified short synthetic shRNAs (sshRNAs) that target a conserved hepatitis C virus (HCV) sequence within the internal ribosome entry site (IRES) of HCV and potently inhibit HCV IRES-linked gene expression. To assess in vivo liver delivery and activity, the HCV-directed sshRNA, SG220 was formulated into lipid nanoparticles (LNP) and injected i.v. into mice whose livers supported stable HCV IRES-luciferase expression from a liver-specific promoter. After a single injection, RNase protection assays for the sshRNA and 3H labeling of a lipid component of the nanoparticles showed efficient liver uptake of both components and long-lasting survival of a significant fraction of the sshRNA in the liver. In vivo imaging showed a dose-dependent inhibition of luciferase expression (>90% 1 day after injection of 2.5 mg/kg sshRNA) with t1/2 for recovery of about 3 weeks. These results demonstrate the ability of moderate levels of i.v.-injected, LNP-formulated sshRNAs to be taken up by liver hepatocytes at a level sufficient to substantially suppress gene expression. Suppression is rapid and durable, suggesting that sshRNAs may have promise as therapeutic agents for liver indications.